2019
DOI: 10.7150/jca.27490
|View full text |Cite
|
Sign up to set email alerts
|

Lung cancer in young adults aged 35 years or younger: A full-scale analysis and review

Abstract: Objectives : Lung cancer in young adults is a distinct disease with particular socioeconomic implications. This study aimed to clarify the clinicopathological characteristics, best interventions, and outcomes of this distinctive entity. Methods : A retrospective review of patients with lung cancer was performed in our institute from January 2010 to June 2017. Young adults were defined as between 18 and 35 years old. Demographic, clinicopathological, therapeutic, and prognosti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
56
1
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(65 citation statements)
references
References 23 publications
6
56
1
2
Order By: Relevance
“…Epidermal growth factor receptor (EGFR) and KRAS activating mutations are the most common genetic alterations in AC. Liu et al [19] in their study on young adults with lung cancer found that 45% of the 82 patients had AC and 49.21% had late-stage (Stage IV) disease at diagnosis. Among the 18 patients for whom EGFR and anaplastic lymphoma kinase (ALK) status was determined, 10 had sensitive EGFR mutations and 5 had ALK rearrangement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Epidermal growth factor receptor (EGFR) and KRAS activating mutations are the most common genetic alterations in AC. Liu et al [19] in their study on young adults with lung cancer found that 45% of the 82 patients had AC and 49.21% had late-stage (Stage IV) disease at diagnosis. Among the 18 patients for whom EGFR and anaplastic lymphoma kinase (ALK) status was determined, 10 had sensitive EGFR mutations and 5 had ALK rearrangement.…”
Section: Discussionmentioning
confidence: 99%
“…Among the 18 patients for whom EGFR and anaplastic lymphoma kinase (ALK) status was determined, 10 had sensitive EGFR mutations and 5 had ALK rearrangement. It is speculated from studies [19] on NSCLC among those aged ≀40 years that frequent genomic alterations occur in this subset. We need to delineate genetic/molecular contributions as marker panels for risk and prognosis of lung cancer, which in-turn will address their application as screening tools in the clinical setting [20].…”
Section: Discussionmentioning
confidence: 99%
“…Literature about the clinical characteristics, pathophysiology, and time trends of young patients with lung cancer is very limited, having only a 1.37% incidence rate in ages of 18 to 35 [ 2 ]. However, one study called the Surveillance, Epidemiology and End Results (SEER) database created in 2010 gives us some insight regarding the diagnosis of NSCLC in young adults.…”
Section: Discussionmentioning
confidence: 99%
“…The timely diagnosis of pulmonary neoplasms in young non-smoking women is notoriously challenging, and most cases are detected as stage IV metastatic disease [ 12 ]. Specifically, the rarity of ASC cases described within this epidemiological profile not only hinders the deployment of diagnostic procedures, but also complicates clinical management decisions and prognostic prediction [ 12 , 13 ]. Therefore, it is crucial to conduct more studies to better inform the clinical, pathologic, and radiographic aspects of lung ASC in these patients.…”
Section: Discussionmentioning
confidence: 99%